2021
DOI: 10.1111/jcpe.13521
|View full text |Cite
|
Sign up to set email alerts
|

On the accuracy, sensitivity, and grading of mouthrinse active matrix metalloproteinase‐8 (aMMP‐8) point‐of‐care testing (POCT)

Abstract: To the Editor, Active matrix metalloproteinase-8 (aMMP-8), used in point-of-care testing (POCT), can be regarded as a potential biomarker for peri-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 28 publications
0
9
0
1
Order By: Relevance
“…Recently, regarding chronic adult periodontitis, two distinct studies addressing the implementation of an aMMP‐8 chairside test as the key chairside biomarker in the new staging and grading classification of periodontitis have yielded varied results (Sorsa et al 2020 , 2021 ). Careful comparison of the clinical status and data of the patient materials involved in these two cohort studies revealed that Deng et al's ( 2021 ) cohort exerted clearly lesser gingivitis cases with lower Gingiva Index (GI) and, that is, with less deep PPD and less increased BOP% values (Deng et al, 2021 ) than the ones in the Sorsa et al's cohort (Sorsa et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, regarding chronic adult periodontitis, two distinct studies addressing the implementation of an aMMP‐8 chairside test as the key chairside biomarker in the new staging and grading classification of periodontitis have yielded varied results (Sorsa et al 2020 , 2021 ). Careful comparison of the clinical status and data of the patient materials involved in these two cohort studies revealed that Deng et al's ( 2021 ) cohort exerted clearly lesser gingivitis cases with lower Gingiva Index (GI) and, that is, with less deep PPD and less increased BOP% values (Deng et al, 2021 ) than the ones in the Sorsa et al's cohort (Sorsa et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Early diagnosis of periodontitis in the group of infertile patients would enable treatment on time, leading to the elimination of inflammatory stimuli. The papers published after the adoption of the new classification of periodontitis in 2018 (27) considered the rapid test for aMMP-8 from oral mouth rinse, as used in present research, a key marker for early diagnosis and monitoring disease activity consistent with the new classification (32,33).…”
Section: Raspravamentioning
confidence: 99%
“…Rana dijagnoza parodonititsa, kad je riječ o neplodnim pacijenticama, omogućila bi pravodobnu terapiju i eliminaciju upalnih žarišta. U radovima objavljenima nakon prihvaćanja nove klasifikacije parodontitisa 2018. godine (27) predlaže se brzi test za aMMP8 iz ispirka usne šupljine, kakav je korišten i u ovom istraživanju, kao ključni biljeg za ranu dijagnozu i praćenje aktivnosti bolesti koja je u skladu s novom klasifikacijom (32,33). Prema našim rezultatima, osjetljivost i specifičnost testa za detekciju parodontitisa u skupini neplodnih pacijentica iznosila je 84 i 72 %, u skupini plodnih pacijentica 88 i 68 % te 86 i 70 % u ukupnoj populaciji pacijentica.…”
Section: Raspravaunclassified
“…An active MMP‐8 (aMMP‐8) point‐of‐care (PoC) test, has been validated across countries in both the adolescent and adult populations as a tool to define active and inactive sites of periodontal disease, evaluate prognosis, and assess patients during the treatment and maintenance phases (Alassiri et al, 2018 ; Heikkinen et al, 2016 ; Izadi Borujeni et al, 2015 ; Johnson et al, 2016 ; Lähteenmäki et al, 2020 ; Leppilahti et al, 2018 ; Lorenz et al, 2017 ; Nwhator et al, 2014 ; Räisänen et al, 2018 , 2019 ; Sorsa et al, 2020 , Sorsa, Grigoriadis et al, 2021 ). This PoC testing methodology, in particular, exhibits a sensitivity of 76%–83% and specificity of 96% with results being reported in a time frame of 5–7 min (Sorsa et al, 2015 , 2017 ).…”
Section: Introductionmentioning
confidence: 99%